Sustainable Development and Demographics a Comparative Study between Urban and Rural Population According to Population Estimates for the Year 2021 - Entesar Kadhim Jasim, Marwah Ali Maklef (Mathematical Statistician and Engineering Applications, 2022)
The population study is one of the important studies which is depended on a lot in planning and decision-making, so in this research, estimates of Iraq’s population for the year 2021 were used for the urban and rural regions and a comparison was made between the results of the two regions through the use of some age categories indicators such as the arithmetic mean of ages, median age, dependency ratio, the youth ratio, and aging ratio, has also been used qualitative composition indicators were used, such as the sex ratio at birth, the sex ratio to the total population, the proportion of males and the proportion of females, and The proportion of the population under the age of thirty- that category had a great role in sustainable development. The Secretariat’s guide of the United Nations was used to check the accuracy of the data. Finally, using the urban and rural population pyramid to determine the population pattern.